Застосування методу проблемної лекції для викладання економічних дисциплін - Романовська, Олена Олександрівна; Яворський, Петро Романович (НТУ "ХПІ", 2012)
The article discusses the theoretical basis of academic problem lectures in teaching economic disciplines, analyzes the factors that hinder the spread of problem-based learning in higher education
Keywords: проблемна лекція; проблемна ситуація; проблемні питання; теорія проблемного навчання